Answer:
5
Step-by-step explanation:
Answer:
f(x)= 3x-4
f(-1)= 3*-1-4
f(-1)= 2-4
f(-1)= -2
f(x)= 3x-4
f(3)= 3*3-4
f(3)= 9-4
f(3)=5
f(x)= 3x-4
f(1)= 3*1-4
f(1)= 3-4
f(1)= -1
Step-by-step explanation:
2 16/100 this would be that as a fraction. I'm a little confused as to what your asking
To factor you have to do this:
s^2 + 9s = -20
+ 20 +20
s^2 + 9s + 20 = 0
now you need to numbers that multiplied give you 20
and then those same 2 numbers have to add to 9
5 x 4 = 20
5+ 4 = 9
(x + 4) (x+ 5)
that means that x= -4, and -5